PENGARUH KINERJA DOSEN, KUALITAS PELAYANAN DAN FASILITAS TERHADAP KEPUASAAN MAHASISWA UNIVERSITAS MUHAMMADIYAH BENGKULU - Islamuddin, Islamuddin; Bahrun, Khairul; Yulinda, Ade Tiara; Nababan, Tongam Sihol (SULTANIST: Jurnal Manajemen dan Keuangan, 2021)
AbstractThis study aims to determine the effect of lecturer performance, service quality and facilities on student satisfaction at the University of Muhammadiyah Bengkulu. The type of research used in this research is descriptive quantitative method. the population in this study were students of the University of Muhammadiyah Bengkulu. The sample used in this study was 637 respondents. Data collection techniques using a questionnaire. The data analysis technique uses Multiple Linear Regression Test, and Hypothesis Testing, namely T Test and F Test. The results of this study can be concluded that the Lecturer Performance variable has a positive and significant effect on Student Satisfaction, Service Quality has a positive and significant effect on Student Satisfaction, then Facilities have an effect on Student Satisfaction, and Lecturer Performance, Service Quality and Facilities together have a positive and significant effect on Student Satisfaction at the University of Muhammadiyah Bengkulu.Â Keywords: Lecturer Performance, Service Quality, Facilities, and Student SatisfactionÂ